4u+3-5(-2u-1)=6(u-1)

Simple and best practice solution for 4u+3-5(-2u-1)=6(u-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u+3-5(-2u-1)=6(u-1) equation:


Simplifying
4u + 3 + -5(-2u + -1) = 6(u + -1)

Reorder the terms:
4u + 3 + -5(-1 + -2u) = 6(u + -1)
4u + 3 + (-1 * -5 + -2u * -5) = 6(u + -1)
4u + 3 + (5 + 10u) = 6(u + -1)

Reorder the terms:
3 + 5 + 4u + 10u = 6(u + -1)

Combine like terms: 3 + 5 = 8
8 + 4u + 10u = 6(u + -1)

Combine like terms: 4u + 10u = 14u
8 + 14u = 6(u + -1)

Reorder the terms:
8 + 14u = 6(-1 + u)
8 + 14u = (-1 * 6 + u * 6)
8 + 14u = (-6 + 6u)

Solving
8 + 14u = -6 + 6u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-6u' to each side of the equation.
8 + 14u + -6u = -6 + 6u + -6u

Combine like terms: 14u + -6u = 8u
8 + 8u = -6 + 6u + -6u

Combine like terms: 6u + -6u = 0
8 + 8u = -6 + 0
8 + 8u = -6

Add '-8' to each side of the equation.
8 + -8 + 8u = -6 + -8

Combine like terms: 8 + -8 = 0
0 + 8u = -6 + -8
8u = -6 + -8

Combine like terms: -6 + -8 = -14
8u = -14

Divide each side by '8'.
u = -1.75

Simplifying
u = -1.75

See similar equations:

| 2x-5*2=10 | | 2y+(5-7y)-9-(3y-2)= | | f(x)=x^3-2.25x^2-3x | | x+2*4=4 | | 427xX=X | | x+0y=4 | | Y+3z=10 | | x-6=-31 | | x(x+3)(x+3)=x(x-3)(x+3) | | 6-4(x+5)=-16 | | K=9r-a | | 2x^2+y^2=17 | | -4(y+5)=8-6(y+7) | | 7y-(8y+9)=10 | | 2x^4+20x^2+18=0 | | 5x=3x-4x+10+2 | | -4(-2)(-5)= | | 4+5=445 | | [(x^3+4X)(6X+2)]+[(3X^2+2X-5)(3X^2+4)]= | | 4+4=445 | | X=(x+500)+4x-1100 | | 2ln(2x)=4-ln(25) | | H=-16x^2+108x+160 | | X=-16x^2+108x+160 | | 5a+4c=7549.47 | | X=2x^2-1600 | | 4x+3=5-2x | | 5a+4c=100 | | 6.1x-3.5=20.9 | | X+3x+5=117 | | 18x+1=5x+2 | | 5(b-9)=12 |

Equations solver categories